1992
DOI: 10.1007/bf02284963
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of human blood platelets to the aggregating agent ADP during different dietary sodium intakes in healthy men

Abstract: We have investigated the effect of varying sodium intake on the renin-angiotensin system, ADP-induced platelet aggregation in vitro, and blood 5-HT concentrations in 9 male volunteers. Systolic blood pressure was slightly reduced during a low sodium diet, whereas the diastolic pressure remained unchanged. Plasma renin activity and aldosterone concentration both fell significantly when sodium intake was increased; plasma angiotensin II concentration also fell, but not significantly. There was a significant fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…After screening titles and abstracts, we selected 462 publications for full text review, of which 329 were excluded for the reasons summarised in figure 1. One hundred and thirty three studies27282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119…”
Section: Resultsmentioning
confidence: 99%
“…After screening titles and abstracts, we selected 462 publications for full text review, of which 329 were excluded for the reasons summarised in figure 1. One hundred and thirty three studies27282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119…”
Section: Resultsmentioning
confidence: 99%
“…We also noted possible discrepancies with respect to the accuracy of data extraction. For example, the included study by Gow and colleagues reported a mean systolic BP of 120 mm Hg in the normal sodium diet group, and Gradual and colleagues reports these data as missing. Table S4 contains errors in sodium intake and BP values for Burnier and colleagues and Heer and colleagues A detailed analysis of all the extracted data has not yet been conducted.…”
Section: Resultsmentioning
confidence: 99%
“…52 Similarly in normal women a change in salt intake from 10 to 200 mmol/day was associated with a significant increase in platelet aggregation. 53 In two groups of men with and without a family history of hypertension a high salt intake increased the blood pressure of those with a family history but platelet aggregation increased in both groups, though it rose more in those with a family history.…”
Section: Plateletsmentioning
confidence: 98%